The effects of Tai Chi on physical function and safety in patients with rheumatoid arthritis: A systematic review and meta-analysis - Wu, Haiyang; Wang, Qiang; Wen, Guowei; Wu, Junhao; Wang, Yiru (Frontiers in Physiology, 2023)
Background: Rheumatoid arthritis (RA) is a chronic, systemic, inflammatory autoimmune disease that results in the destruction of joints, connective tissues, muscle, tendons and fibrous tissue. Until now, there are no cure therapies. Objective: We aimed to assess the effectiveness of Tai Chi (TC) on physical function and safety of RA patients by meta-analysis. Methods: The PubMed, Cochrane Library, EMBASE, web of science, China National Knowledge Infrastructure and Google Scholar were searched up to January 2023. We included randomized controlled trials (RCTs) or controlled clinical trials (CCTs) comparing TC to control conditions for RA patients. Review Manager (Version 5.3) software was used to analyze outcomes of time to walk 50 feet, joint tenderness, number of swollen joints or tender joints, handgrip strength, pain, the Health Assessment Questionnaire (HAQ) and withdraws overall. Results: A total of 351 patients with RA from 6 RCTs and 3 CCTs were included for meta-analysis. TC could also significantly decrease withdrawals overall in studies (OR=0.28, 95% CI 0.13 to 0.64, P= 0.002). No significant treatment effects of physical function were identified of the other outcomes. Conclusion: Our findings indicated that TC was safe to RA patients, but it can not improve physical function and pain. However, there is still lack of more evidence.